The Japanese Government–NGO Relationship in the Foreign Aid Field: “Partnership” Reconsidered - Szczepanska Kamila (The Committee of Oriental Studies of the Polish Academy of Sciences and The Publishing House ELIPSA, 2026)
This article re-examines the notion of “partnership” and its applicability to the relationship between the Japanese government and domestic NGOs in the context of foreign aid. As such, it provides empirical insights on government-non-profit relationship in understudied policy field of foreign aid in East Asian context. Illuminating how governmental financial support for Japanese NGOs has evolved in recent years, the article concludes that whereas “partnership” may be a preferred term of the Japanese government to describe the relationship with Japanese NGOs, the manner in which it is operationalized through selected financial support schemes raises legitimate questions about the validity and applicability of this particular term to the case under investigation. Hence, the chosen financial assistance schemes serve as the lenses through which the article explores and assesses the official “partnership” assertions. In sum, the relationship suffers from shortcomings in terms of mutuality and organizational identity, qualifying both the extent and quality of government-sponsored opportunities for Japanese international cooperation NGOs.